Improving the Performance of Diamond Grinding Tool by Modifying the Synthetic Diamond Surfaces - LAVRINENKO, V.; BOCHECHKA, O.; POLTORATSKYI, V.; SMOKVYNA, V.; SOLOD, V. (Science and Innovation, 2024)
Introduction. Machine-building enterprises of Ukraine need a highly effi cient diamond grinding tool. For its eff ective use, it is necessary to use high-quality synthetic diamond powders with improved operational characteristics. Problem Statement. Among the disadvantages of synthetic diamonds used in grinding tools is their oxidation under high temperature, during high-performance grinding of modern hard-to-machine materials. Purpose. The purpose of this research is to study the possibilities of improving the operational characteristics of the diamond grinding tool by modifying the surface of synthetic diamond grains. Material and Methods. The surface of AC6–АС20 diamond powder has been modifi ed by the isothermal method of liquid-phase deposition of heat-resistant oxides (B2O3, Al2O3), chlorides (CaСl2, NaCl, MgCl2, FeCl3), and their mixes (B2О3 + CaСl2, B2О3 + NaCl) from saturated solutions on the diamond surface. Results. The basic technology of forming heat-stable wear-resistant coatings on the surface of diamond grinding powder grains from mixes of soluble and insoluble oxygen- (B2O3, TiO2, SiO2, Al2O3, TiO, CaO, ZnO, CeO2, SnO2), silicate- (Na2O(SiO2)n), (K2O(SiO2)n) and carbide- containing (SiC, TiC, B4C) compounds in various combinations. It has been found that the modifi cation allows reducing the costs of diamonds in grinding wheels, with the best solution being the modifi cation with B2O3 and Al2O3 oxides. It has been shown that the modifi cation of the surface of diamond grains with the combination of B2O3/Al2O3 allows improving the fi lling of the rough polished surface with material and increasing its holding capacity. It has been established that with an increase in the manufacture cost by as few as 9—11%, the modifi cation of abrasive grains of grinding wheels enhances the wheel wear resistance 2 times. Conclusions. The use of such purposefully improved diamond grinding powders in the working layer of diamond wheels allows increasing the performance and wear resistance of the diamond grinding tool.